Geohazard features of the Northern Sardinia - Alessandro Conforti; Francesca Budillon; Giovanni De Falco; Giacomo Deiana; Valentino Demurtas; Gabriella Di Martino; Sara Innangi; Antonietta Meleddu; Paolo Emanuele Orrù; Enrico Pagliaga; Simone Simeone; Renato Tonielli (Journal of Maps, 2024)
The maps of the geohazard-related features of the North Sardinia continental margin produced by the Magic project (MArine Geohazard along Italian Coasts) are here presented. The maps were created on the base of morphobathymetric data obtained by with multibeam echo sounders. ThreCoNISMa, DSCG Università degli studi di Cagliari, Cittadella Universitaria Monserrato - S.P. Monserrato-Sestu, Monserrato (CA), Italye wide canyon systems, Castelsardo to the west, Lavezzi and Caprera to the east, originate from the continental shelf between the islands of Sardinia and Corsica and run toward the Sardinia Sea and the Tyrrhenian Sea, respectively. The canyons feature very wide and articulated heads, meandered sections of the main axis. The continental shelfhosts several coastal lithotomies, genetically related to late Quaternary sea-level oscillation and coastline migration. Furthermore, in the Bonifacio Strait, several bedform fields testify to the present-day activity of strong bottom currents. The main geohazard potential from the North Sardinia is related to the retreating of Castelsardo canyon heads, in offshore of Castelsardo and Asinara, which cuts the continental shelf reaching a few kilometers from the coast.